Who belongs to the swiss body politique—A diaspora perspective - King-Savic, Sandra (Frontiers in Political Science, 2023)
In this paper, I try to better understand the intersection between “integration” in legal terms, and how long-term resident “non-citizens” and migrants from the former Socialist Federal Republic of Yugoslavia (SFRY) situate themselves in narratives of belonging vis a vis the normative power structure that constitutes the Swiss body politique. More specifically, how do labor and forced migrants from former Yugoslavia negotiate the shifting understanding of “integration” in Switzerland in legal and social terms? Former Yugoslavs constitute not only a comparatively large number of “non-citizens” in Switzerland, but individuals from-and-with-connections to this community also embody numerous labels and categories of migrant that statistical databases, the media, and legal practices attach to them since the 1970s. Key findings in this paper illustrate a two-tiered narrative: “non-citizens” seemed to have maintain(ed) their pursuit of not attracting attention to their persona—a strategy that allowed individuals to disappear within the larger society. Ensuing Europeanization processes, coupled with the Wars of Yugoslav Succession during the 1990s, however, brought to the fore “a politics of rupture” that called into question othering processes, and the seemingly tightening sociolegal basis of belonging to the Swiss body politique. Hitherto examined data suggests that interlocutors pursue a “positive essentialist frame” to counter exclusionary narratives “non-citizens” experience to postulate “rights claims”. Interviewees, in other words, activate diaspora connections and networks to support and aid each other when legal and socio-political questions arise, but also to actively influence the political and legal landscape in Switzerland.